Fault Tolerance Middleware Cloud Computing In Virtual Infrastructures - Sathishkumar, D; Vadivel, R (International Journal of Computer Sciences and Engineering, 2022)
As cloud computing becomes more popular as an attractive alternative to traditional information processing systems, accurate and continuous operation is becoming more important, even in the presence of faulty components. This white paper presents an innovative modular system-level perspective for building and managing cloud fault tolerance. It uses a dedicated service layer to provide application developers and users with a comprehensive, high-level approach to hiding the details of implementing fault-tolerance techniques. In particular, the service layer allows users to specify and apply the required level of fault tolerance without the need for knowledge of the fault-tolerance technologies available in the desired cloud and their implementation. Use run-time monitoring to determine the mechanism and characteristics of your fault-tolerance solution. Based on the proposed approach, design a framework that easily integrates with your existing cloud infrastructure and makes it easier for third parties to provide fault tolerance as a service. Our goal is to work directly at the VM instance level of Virtual Machine Manager and inject the framework as a dedicated service layer between the application and the hardware. Fault Tolerance Manager addresses the issue of computing resource inhomogeneity, achieves the goal of transparently providing fault tolerance support for node failures to user applications, and achieves scalability and interoperability goals. To overcome these challenges, we propose to build a fault tolerance manager according to the principles of service-oriented architecture.